INTERPRETATION OF TUNNEL HAZARD WARNING LEVELS BASED ON INTACT ROCK COMPRESSIVE STRENGTH DATA TO DETERMINE THE STRESS EXPERIENCED BY THE SURROUNDING ROCK - Iqbal Reza Arifin, M.
Based on the HWL presentation, several tunnel failured occurred when the measured strain did not match the HWL graph. This may be due to a lack of comprehensive expansion of the database used to interpret each level line on the HWL. This study analyzes stress levels in rocks by plotting data from 1162 laboratory-scale compressive strength tests (UCS) on the Sakurai graph, and then interpreting Hazard Warning Levels (HWL) based on these results. This research aims to provide insight into the rock types found in Indonesia. The stress-strain parameters are adjusted through trial and error to fit the graph, and the resulting HWL interpretation is validated using a 2D numerical simulation of a basic tunnel. If the validation results do not match, modifications will be made to the Sakurai Hazard Warning Levels graph. After analyzing the 3 levels on the Hazard Warning Levels graph, interpret the 3 levels of stress experienced by the intact rock on the stress-strain curve, and at each level shows the percentage of Ci where level III = 80% UCS; level II = 40% UCS; level I = 20% UCS. The stress-strain curve obtained from the uniaxial compressive strength test shows a 90% accuracy level in predicting tunnel stability.